ИСПОЛЬЗОВАНИЕ СИСТЕМ КОНТРОЛЯ ДЛЯ УПРАВЛЕНИЯ ТЕМПЕРАТУРНЫМИ ПРОЦЕССАМИ - ТОШПУЛАТОВ КОБИЛ ЯХЪЁХОН УГЛИ, АБДУЛАХАДОВ АБДУХАЛИЛ АБДУВАЛИ УГЛИ (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article examines the effectiveness of the use of control systems in the management of temperature processes. Control methods used in various industrial sectors are examined in detail, their benefits are analyzed and the results are evaluated in the context of optimization of thermal processes. The findings have important implications for improving the efficiency and stability of process systems, highlighting the importance of applying modern control techniques in engineering applications.